Wildlife and zoo nursing at The Nest Te Kōhanga (Wellington Zoo Hospital). Issue 6 (2nd June 2016) - Dean, Catherine
ABSTRACT: This is a review of volunteering as a veterinary nurse at The Nest Te Kōhanga, Wellington Zoo, with the focus on conservation, sustainable practices and the difficulties that come with zoo and wildlife nursing in terms of evidence-based research. Many similarities can be found between the job roles of a small animal veterinary nurse and a wildlife or zoo veterinary nurse, and these are discussed.